Critical thinking level of undergraduate nursing students from first and last semesters in a university of Medellín-Colombia - Salazar-Blandón, Diego Alejandro; Ospina-Rave, Beatriz Elena (Universidad y Salud, 2019)
Introduction: Critical thinking is an important component of nursing education. Different organizations demand critical thinking strategies to accredit university programs. However, there is little evidence on the measurement of their levels. Objective: To compare the level of critical thinking in students of first and last semester of Nursing in a university of Medellin-Colombia, in 2016. Materials and methods: Descriptive, cross-sectional and comparative quantitative study in a sample at the convenience of first-year students and last semester. Results: In both groups, the level is medium (first 44.47, last 53.14 p <0.001). However, an increase of 19.49% is observed with respect to the first semester, with significant changes in the domains: evaluation, argumentation and interpretation. No differences were found in the inference and analysis domains. Conclusions: The findings show a positive change in the level of critical thinking, which is a starting point for the analysis of the teaching-learning process in the faculty where the study was developed, in order to strengthen the domains where significant increases were observed and develop strategies that favor the development of skills in which no changes were observed. It is important to develop investigations with longitudinal measurements and reliable instruments.